Analysis of Kansas Hog Enterprise returns from 1981-1990 - Michael R Langemeier (Kansas Agricultural Experiment Station Research Reports, 1990)
Estimated historical return distributions for farrow-to-finish, feeder pig finishing, and feeder pig producing operations in Kansas from 1981-1990 were examined. Average returns per head were the highest and downside risk was the lowest for farrow-to-finish operations over this period. However, the required investment in buildings, equipment, and breeding stock per head was also higher for this operation. Thus, a tradeoff exists between returns per head and capital requirements per head.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Enterprise; Records; Economics